Gender differences in the behavioral component of social intelligence of children with special educational needs - Kots , Mykhailo; Duchyminska, Tamara; Polycarchik , Sofia (Psychological Prospects Journal, 2021)
Purpose. The aim of the article is theoretical analysis and empirical study of gender differences in the behavioral component of social intelligence of children with special educational needs. Methods. The sample consisted of students in grades 7-11 at the Education and Rehabilitation Center. The total sample size is 60 people: 36 boys and 24 girls. To conduct an empirical study were used: questionnaire "Social Adaptability", test "Determining the style of behavior in a conflict situation" (K. Thomas, adaptation of N. Grishina), Snyder self-monitoring scale. Results. The paper show that boys are more socially adapted than girls. This is primarily due to the environment in which children with special educational needs study. It is confirmed that the optimal level of self-monitoring is most pronounced in boys, while a high level prevails in girls. This indicates that the phenomenon of self-monitoring is more developed in boys than in girls. Conclusions. The data clarify the relationship between styles of behavior in conflict situations and the level of self-monitoring of children with special educational needs, as well as between the level of social adaptation and behavioral styles of girls. Prospects for further research in conducting an empirical study of the personal sphere of children with special educational needs, studying the root causes, forms and manifestations of behavioral disorders with a view to their early diagnosis and correction.